Aesthetic site development for a restorative- driven implant placement in a young patient with nasopalatal lateralization: a case report - de Anda Hidalgo, Adriana Fernanda; Hernandez Diez de Sollano, Guillermo Manuel (International Journal of Research in Medical Sciences, 2025)
This case report details the management and importance of site development in the anterior zone in a 22-year-old patient, looking for a good long-term prognosis and aesthetic result. The absence of a central incisor from a young age created an altered nasopalatine conduct that would have impede the placement of an implant. In order to achieve an adequate aesthetics and long-term prognosis, a step-by-step treatment plan was established. The treatment approach included a diagnostic mock-up, periodontal therapy, crown lengthening, nasopalatal lateralization, implant placement and a screw retained crown. The post-operative course showed satisfactory recovery with no complications. This case highlights the effectiveness of a multidisciplinary approach in managing complex anterior zone cases.